2012
DOI: 10.1007/s00020-012-2025-1
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Norm of Operators on $${A^p_\alpha(\mathbb{B}_n)}$$

Abstract: In this paper we characterize the compact operators on A p α (B n ) when 1 < p < ∞ and α > −1. The main result shows that an operator on A p α (B n ) is compact if and only if it belongs to the Toeplitz algebra and its Berezin transform vanishes on the boundary of the ball.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…A version of this result in the classical Bergman space setting was first proved by Suárez in [31]. Related results were later given in [4,20,22,25]. …”
Section: Reproducing Kernel Thesis For Compactnessmentioning
confidence: 74%
See 3 more Smart Citations
“…A version of this result in the classical Bergman space setting was first proved by Suárez in [31]. Related results were later given in [4,20,22,25]. …”
Section: Reproducing Kernel Thesis For Compactnessmentioning
confidence: 74%
“…For the proof see [21]. Related results can be found in [4,8,22,31] where it is shown that nice domains, such as the unit ball, polydisc, or C n have this property.…”
Section: Projection Operators On Bergman-type Spacesmentioning
confidence: 84%
See 2 more Smart Citations
“…The behaviour of these operators on the Hardy spaces, Bergman spaces, and Fock spaces has been studied widely and a lot of results are available in the literature. The characterization of compactness has been studied in [2][3][4][5][6][7][8] just to cite a few. Given Ω ⊂ R , a measurable function : Ω → [1, ∞) will be called a variable exponent.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%